2020
DOI: 10.1002/capr.12342
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual counselling mitigates loneliness and promotes affect balance for older empty nester couples: A study in some international cities

Abstract: This article reports a study examining the impact of a spiritual counselling programme (SCP) on older empty nester couples' loneliness experiences and affect balance. Since empty nesters are usually couples with a greater likelihood of interdependence in the psychosocial domains, there is a need to examine interdependent effects or actorpartner interdependent effects of interventions. Twenty-four online SCP sessions were conducted throughout the year with the intervention group couples who were assessed on lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In this study, it was found that there was a negative significant relationship between loneliness and spiritual well-being levels of Type 1 and Type 2 diabetic patients. In some studies, like the current study, it was found that spiritual well-being reduces loneliness (Dashtbozorgi et al, 2016 ; Gallegos & Segrin, 2019 ; Pandya, 2020 ). It can be said that spirituality is effective in reducing the loneliness of diabetic patients.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In this study, it was found that there was a negative significant relationship between loneliness and spiritual well-being levels of Type 1 and Type 2 diabetic patients. In some studies, like the current study, it was found that spiritual well-being reduces loneliness (Dashtbozorgi et al, 2016 ; Gallegos & Segrin, 2019 ; Pandya, 2020 ). It can be said that spirituality is effective in reducing the loneliness of diabetic patients.…”
Section: Discussionsupporting
confidence: 59%
“…In this study, it was found that there was a negative significant relationship between loneliness and spiritual wellbeing levels of Type 1 and Type 2 diabetic patients. Other published studies indicated that spiritual well-being reduced loneliness (Dashtbozorgi et al, 2016;Gallegos & Segrin, 2019;Pandya, 2020).…”
Section: Resultsmentioning
confidence: 97%
“…This type of support meets the needs of those who feel the need to engage with someone who can also understand the meaning of their faith, responding to issues that others are unable to consider. This type of matching increases psychological well-being (Maynard & Snodgrass, 2015 ) and self-awareness (Pandya, 2020 ). All of this allowed the participants in the present study to reduce the anxiety produced by the COVID-19 pandemic by counteracting feelings of loneliness fear, and boredom.…”
Section: Discussionmentioning
confidence: 99%